A mathematical modelling of a Atherosclerosis intimation with Atangana-Baleanu fractional derivative in terms of memory function - Yao, Shao-Wen; Faridi, Waqas Ali; Asjad, Muhammad Imran; Jhangeer, Adil; İnç, Mustafa (Elsevier, 2021)
Fractional calculus can provide a concise model for the description of the physical events that occur in inflammatory process. This work aims to investigate and construct a mathematical model of the control and inflammatory process during atherosclerosis disease utilizing the fractional theory of differentiation. For this purpose, the Atangana-Baleanu fractional operator in sense of Caputo is applied to systematized the atherosclerosis disease in the presence of memory function instead of initial conditions that permits us to generalize the proposed model. The existence of an obtained solution is discussed and the qualitative analysis is carried out for the proposed model which shows that the obtained solution is unique. The authors are confident about the generated mathematical fractional-order atherosclerosis inflammation model. We hope that the proposed fractional-order model will be more effective and helpful in the detection of atherosclerosis inflammation disease. The consequences shown in this paper might stir a new idea for tests and experiments in the future.
Keywords: Mathematical modelling; Fractional calculus; Reaction-diffusion equation; Atherosclerosis